The influence of light intensities and micropollutants on the removal of total coliforms and E. coli from wastewater in a flat-panel photobioreactor - Pompei, Caroline Moço Erba [UNESP]; Ruas, Graziele [UNESP]; Bolzani, Hugo Renan [UNESP]; Fernandes, Luiza Maria [UNESP]; Silva, Gustavo Henrique Ribeiro da [UNESP] (Elsevier, 2024)
The presence of micropollutants and pathogens in sanitary wastewater and surface water is a growing concern that impacts public health, environmental balance and the maintenance of water supply services. To improve sanitary wastewater treatment, it is necessary to develop and improve sustainable technologies. Among the available options, microalgae-based systems stand out for their efficiency and generation of value-added byproducts. To study the impact of luminosity and the presence of micropollutants (13 selected) on the removal of E. coli and total coliforms from real anaerobically treated wastewater, a pilot flat-panel photobioreactor (50 L) was operated in batch mode in a tropical climate region. This is the first study to evaluate whether micropollutants interfere with coliform groups, considering a microalgae-based system and an experiment in a tropical climate region. E. coli had better removal (from 104 to 101 CFU 100 mL−1) than did total coliforms (from 104 to 103 CFU 100 mL−1). The removal of E. coli was more strongly linked to luminosity and temperature, while the removal of total coliforms was influenced by the presence of the selected micropollutants.